Comparison of Prostaglandin E2 And Misoprostol for Induction in Second Trimester Miscarriage in Patients Presented in Independent University Hospital Faisalabad - Khan, Zara Gul (Indus Journal of Bioscience Research, 2025)
Objectives: To compare the efficacy of Misoprostol and Prostaglandin E2 (PGE-2) for induction in second-trimester miscarriage, considering demographic and clinical factors. Study Settings: This randomized controlled trial was conducted at the Department of Gynecology, Independent Medical University, Faisalabad, over six months. Duration of Study: The study was conducted after ethical approval and spanned six months. Data Collection: A total of 130 women aged 18-40 years with a gestational age of 13-28 weeks requiring second-trimester pregnancy termination due to intrauterine fetal demise (IUD) or missed miscarriage were included. Participants were randomized into two groups: Misoprostol group (n = 65): Received 50 mcg Misoprostol orally every 4 hours, up to five doses if needed. PGE-2 group (n = 65): Received 0.5 mg PGE-2 intra-vaginally, up to three doses if needed. Efficacy was defined as complete abortion (expulsion of all products of conception), confirmed via ultrasound 12 hours post-treatment. Results: The mean age was 29.32 ± 6.78 years (Misoprostol) vs. 27.25 ± 6.53 years (PGE-2). The majority had a gestational age of >18-28 weeks (78.5% Misoprostol, 55.4% PGE-2). Parity was 0-3 in 81.5% (Misoprostol) and 58.5% (PGE-2). The induction-to-delivery time was similar (12.11 ± 3.12 hours for Misoprostol vs. 12.29 ± 2.83 hours for PGE-2). However, the Misoprostol group required more doses (3.23 ± 1.44 vs. 1.91 ± 0.82, p < 0.05). Complete abortion was achieved in 95.4% of Misoprostol cases vs. 76.9% of PGE-2 cases. Incomplete abortion occurred in 4.6% of Misoprostol patients vs. 23.1% of PGE-2 patients. Misoprostol showed a significantly higher success rate in patients >30 years (p = 0.005) and gestational age >18-28 weeks (p = 0.002). Conclusion: Misoprostol is more effective than PGE-2 for second-trimester miscarriage induction, demonstrating higher efficacy, shorter induction-to-delivery times, and a favorable safety profile. Given its cost-effectiveness and ease of administration, Misoprostol should be considered the preferred agent for second-trimester pregnancy termination.